The Undergraduate Students’ Pronunciation Difficulties of English Fricatives Based on Letter-Sound Relationship - Tri Angkarini (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2023)
This study aims to identify the pronunciation issues with English fricatives that undergraduate students encounter as a result of the intricate link between the English letter and sound. The purpose of this study is to gather comprehensive data regarding students' pronunciation difficulties in terms of the degree of difficulty associated with each English fricative sound, as well as the types of words in which they occur (monosyllabic words, disyllabic words, and multisyllabic words). In order to explain the English sounds that were contributing to the students' pronunciation issues, a descriptive qualitative method was adopted in this study. The information was gathered by recording students speaking 48 words with English fricatives. The results showed that sound /θ/ accounts for 93,9% of the challenges, followed by sound /v/ at 81,8% and sound /ð/ at 60,6%. The main cause of the students' difficulties is the irregularity of the letter-sound relationship and this can be prevented by altering the teaching strategy and making use of listening practice.